2021
DOI: 10.1186/s12199-021-00946-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower albumin levels are associated with frailty measures, trace elements, and an inflammation marker in a cross-sectional study in Tanushimaru

Abstract: Background There is little data on the association between the lower nutrition represented by serum albumin levels and related factors in a general population. The present study aimed to determine whether the albumin level positioned as some kind of biomarker with frailty measures, trace elements, and an inflammation marker. Methods In 2018, we performed an epidemiological survey in 1368 subjects who resided in Tanushimaru, Japan, in which we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…For uric acid and albumin biomarkers, no significant differences were found between the frail and other groups [ 78 ]. Decreased albumin values in clinical settings are associated with nutritional deterioration and inflammatory response associated with the disease, which could be the result of the aging process; however, more studies are still needed to establish this correlation with frailty [ 158 ].…”
Section: Blood Biomarkers Associated With Frailtymentioning
confidence: 99%
“…For uric acid and albumin biomarkers, no significant differences were found between the frail and other groups [ 78 ]. Decreased albumin values in clinical settings are associated with nutritional deterioration and inflammatory response associated with the disease, which could be the result of the aging process; however, more studies are still needed to establish this correlation with frailty [ 158 ].…”
Section: Blood Biomarkers Associated With Frailtymentioning
confidence: 99%
“…Its main function is regulating the colloidal osmotic pressure of blood. Low Alb levels, even within the normal range, are associated with weakness, trace elements, and inflammatory markers in the general population ( 43 ). Compared with Alb, prealbumin (Ttr) has a shorter half-life, faster liver synthesis rate, and predictable catabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 An epidemiological survey found that lower albumin levels, even within the normal range, were related factors of frailty measures, trace elements, and inflammation markers in the general population. 51…”
Section: Discussionmentioning
confidence: 99%